Discovery of habitat preferences and community structure of Echinoderms in Kri, Raja Ampat, Indonesia - RIMA HERLINA SETIAWATI SIBURIAN; JULIA ROSEMARY TAPILATU; MARYROSE EASTER TAPILATU (Society for Indonesian Biodiversity, 2023)
Abstract. Siburian RHS, Tapilatu JR, Tapilatu ME. 2023. Discovery of habitat preferences and community structure of Echinoderms in Kri, Raja Ampat, Indonesia. Biodiversitas 24: 3968-3976. Raja Ampat, located in Papua, Indonesia, is home to one of the most diverse coral reef ecosystems and is a component of the Coral Triangle. The coral in Raja Ampat is still considered to be in good health. Although the marine fauna in Raja Ampat is pristine and diverse, there have still only been a few studies in this region. The scientific research on the Echinoderms in Raja Ampat is limited, particularly as a primary input for data research. In this study, we present Echinoderm's habitat and community structure in the Kri coastal area at Mansuar Island based on the data collected at field sampling. From January to February 2023, data were collected intensively during morning and afternoon low tide for three repetitions each, at 5-10 m depths. We conducted morphological species identification. Asteroidea, Holothuroidea, Echinoidea, and Crinoidea were found to be the four major classes of Echinodermata that dominated the sampling area, with a total of 20 species and 180 individuals. Each Echinodermata species has its preferred Kri coastal habitat based on its food supply, unique behavior, and body structure. In addition, the result indicates that this region has a moderate diversity level, with low dominance and moderate to high uniformity. This research provides new information on the ecology of Echinoderms in eastern Indonesia, particularly in Raja Ampat.